Two new taxa of Impatiens L. (Balsaminaceae) from Western Ghats of India - Prabhukumar, K. M.; Omalsree, M.; Hareesh, V. S.; Bhaskar, V.; Nirmesh, T. K.; Sreekumar, V. B.; Balachandran, Indira (Phytotaxa, 2015)
Two new taxa of Impatiens (Balsaminaceae), viz., I. sasidharanii sp. nov. and I. sasidharanii var. hirsuta var. nov. are described and illustrated from the southern Western Ghats of India. Detailed notes on description, ecology, distribution, morphological variations and IUCN status are provided along with illustrations.